Cytokine-Mediated Induction and Regulation of Tissue Damage During Cytomegalovirus Infection - Clement, Mathew; Humphreys, Ian R. (Frontiers in Immunology, 2019)
Human cytomegalovirus (HCMV) is a β-herpesvirus with high sero-prevalence within the human population. Primary HCMV infection and life-long carriage are typically asymptomatic. However, HCMV is implicated in exacerbation of chronic conditions and associated damage in individuals with intact immune systems. Furthermore, HCMV is a significant cause of morbidity and mortality in the immunologically immature and immune-compromised where disease is associated with tissue damage. Infection-induced inflammation, including robust cytokine responses, is a key component of pathologies associated with many viruses. Despite encoding a large number of immune-evasion genes, HCMV also triggers the induction of inflammatory cytokine responses during infection. Thus, understanding how cytokines contribute to CMV-induced pathologies and the mechanisms through which they are regulated may inform clinical management of disease. Herein, we discuss our current understanding based on clinical observation and in vivo modelling of disease of the role that cytokines play in CMV pathogenesis. Specifically, in the context of the different tissues and organs in which CMV replicates, we give a broad overview of the beneficial and adverse effects that cytokines have during infection and describe how cytokine-mediated tissue damage is regulated. We discuss the implications of findings derived from mice and humans for therapeutic intervention strategies and our understanding of how host genetics may influence the outcome of CMV infections.